Roles of Progressive Malaysian Farmers in Rural Development: A Gender Analysis - Ismail, Maimunah (Universiti Putra Malaysia Press, 1995)
The paper analyses characteristics of men and women progressive farmers and examine their roles in Malaysian rural development. Data were gathered from thirteen male and female winners of the "Farmer of the Year" national award, from 1981 to 1992, using indepth interviews. Male and female progressive farmers have similar characteristics in terms of age and land acreage owned. They differ in terms of educational allainment, family size, and number of leadership positions in institutions. The study showed that both groups perform multiple roles in rural development including involvement in the commercialization of agriculture, agribusiness and non-agricultural business, leadership roles in institutional development, community welfare services, and as local change agents. However, the study showed men and women exhibited some variations in exercising those roles.